Enforcement Measures and Tax Compliance: The Case of Small and Medium Enterprises (SMEs) in Mavoko Sub- County, Machakos County, Kenya - Mwanzia, Stephen Ndua; Musa, Grace; Kiriinya, Stephen (Journal of Accounting, 2025)
Purpose: The primary objective of this study was to find out how tax enforcement measures affected the level of tax compliance among Small and Medium Enterprises (SMEs) operating in Mavoko Sub-County, Machakos County, Kenya. The study further sought to establish the moderating role of government policy on the relationship between enforcement measures and tax compliance among the selected group of SMEs. Methodology: Led by the positivism philosophy, the researchers employed an explanatory and descriptive survey research design to collect primary data from a sample of 376 respondents drawn from a target population of 18,000 SMEs. The data, collected through a structured questionnaire, was analyzed using descriptive statistics to obtain arithmetic means and standard deviations, and through the inferential statistical method of multiple linear regression analysis. The researchers used the Statistical Packages for Social Sciences (SPSS) version 29 software when analyzing the data. Findings: The study established that the tax enforcement measures of tax audits, tax penalties, and publicity of enforcement actions had a statistically significant effect on tax compliance among the identified SMEs. In addition, government policy was found to have a significant moderating role on the relationship between tax enforcement measures and tax compliance. Unique Contribution to Theory, Policy and Practice: The study provides practical recommendations to SMEs on the importance of record keeping and bookkeeping practices for ease and convenience in making tax returns. Secondly, the study presents recommendations to the Kenya Revenue Authority (KRA) that are aimed at enhancing tax compliance among SMEs. In addition, the study offers valuable policy insights for the government of Kenya to encourage voluntary tax compliance in the formal and informal sectors of the economy.